Amount or intensity? Potential targets of exercise interventions in patients with heart failure with preserved ejection fraction. (6th December 2017) - Bobenko, Anna; Bartels, Inke; Münch, Marlene; Trippel, Tobias; Lindhorst, Ruhdja; Nolte, Kathleen; Herrmann‐Lingen, Christoph; Halle, Martin; Duvinage, André; Düngen, Hans‐Dirk; Gelbrich, Götz; Tschöpe, Carsten; et al.
Abstract: Aims: Heart failure with preserved ejection fraction (HFpEF) remains a common condition with no pharmacological treatment. Physical activity (PA) improves symptoms and quality of life (QoL), but no clear recommendations exist on PA in HFpEF patients. We investigated the association of PA (amount/intensity) on clinical phenotype in HFpEF. Methods and results: The Aldosterone in Diastolic Heart Failure trial investigated spironolactone vs. placebo in stable HFpEF patients. At baseline, all patients underwent detailed phenotypization including echocardiography, cardiopulmonary exercise testing, 6 minute walking test (6MWT), and QoL assessment (36‐item Short‐Form questionnaire). PA was assessed by a self‐report questionnaire, classified in metabolic equivalents of task (MET) and analysed with regard to exercise capacity, diastolic function, and QoL. Four hundred twenty‐two patients (52% women, age 67 ± 8 years, New York Heart Association II and III) were classified by weekly MET hours into a low (<70), middle (70–140), or high (>140) level of PA. Total PA correlated positively with 6MWT distance ( r  = 0.17; P  = 0.002) and physical function of QoL ( r  = 0.10; P  = 0.05), but not with peak oxygen uptake (peakVO2 ). In contrast, both 6MWT distance and peakVO2 were significantly higher in patients who performed high‐intensity PA for >8 h/week ( P  < 0.001, P  = 0.02, respectively). Time of high‐intensity PA was related to higher 6MWT distance ( r  = 0.21, P  < 0.001), peakVO2, and better physical function of QoL (both r  = 0.13, P  = 0.01), whereas low‐intensity PA did not show significant associations. Interestingly, PA was not related to any measure of diastolic function. Conclusions: A higher amount of PA is related to higher submaximal exercise capacity and physical function of QoL. Regarding maximal exercise capacity, only high‐intensity PA showed significant association in HFpEF patients.